Characteristics of amyloid‐PET‐negative/tau‐PET‐positive individuals: Neuroimaging / differential diagnosis. (7th December 2020) - Yoon, Bora; ,
Abstract: Background: Little is known about tauopathy without β‐amyloid (Aβ) (A‐T+). Since the introduction of the term primary age‐related tauopathy (PART) several clinicopathological studies have revealed the characteristics of this syndrome. We performed this study of people characterized as A‐T+ with PET biomarkers to describe these individuals, and to determine how such individuals did or did not reflect characteristics of AD. Method: We included 506 nondemented participants from the ADNI dataset. We used Aβ ( 18 F florbetapir or florbetaben) and tau ( 18 F‐AV1451) PET. We subdivided them into 3 groups (A‐T‐ 324 vs A‐T+ 55 vs A+T+ 127) using predefined thresholds for Aβ (A) and tau (T). We compared these groups by demographics, brain amyloid, brain tau level and distribution, hippocampal volumes, and cognition. Result: The A‐T+ group was the oldest among the 3 groups and showed a prevalence of the apolipoprotein E (APOE) ɛ4 genotype similar to A‐T‐ and lower than A+T+. Both the proportion of individuals who were diagnosed with mild cognitive impairment (MCI) and the severity of tau deposition in the A‐T+ group was intermediate between A‐T‐ and A+T+. There was no evidence of even subtly elevated Aβ in the A‐T+ group. A‐T+ showed no asymmetry of tau deposition, and the brain region with the highest tau deposition was the amygdala in both A‐T+ and A+T+ groups (Figure 1). However, the A+T+ group showed a more widespread distribution of tau including temporal, parietal, and occipital areas compared to A‐T+ (Figure 1). Hippocampal volumes (Figure 2) and cognition (Figure 3) were also intermediate to A‐T‐ and A+T+ after adjustment by age, sex, and education. In the A‐T+ group, tau deposition showed a negative association with hippocampal volume and cognition. Conclusion: There is no clear evidence that the A‐T+ group is on the AD continuum. Brain Aβ shows no evidence of elevation and APOE genotypes do not show a high prevalence of ɛ4. These individuals are intermediate between A‐T‐ and A+T+ on most characteristics. Such individuals could reflect PART, although longitudinal follow‐up will be necessary to confirm whether any proportion develops overt Aβ‐positive dementia consistent with AD.